Taking Stock, December 2018 : An Update on Vietnam's Recent Economic Developments - World Bank (World Bank, Hanoi, 2018)
The external environment has become less sanguine and more uncertain. Global real GDP growth is forecast to moderate from a projected 3 percent in 2018 to 2.9 percent in 2019 and 2.8 percent in 2020, as economic slack dissipates, central banks unwind policy accommodation, and global trade and investment growth weaken with deepening trade war tensions among major economies. Following a recent peak of 6.6 percent in 2017, GDP growth in emerging East Asia and the Pacific is forecast to ease from a projected 6.3 percent in 2018 to 6.0 percent in both 2019 and 2020, largely tied to a falloff in exports amid rising trade tensions and a structural slowdown in China.